Critical Employment, Ethical, and Legal Scenarios in Human Resource Development - Hughes, Claretha (Open textbook library., 2020)
This book provides mini-cases for HRD and other disciplines to use for engaging students in incident discussions. Exploring ways to solve problems and make decisions about situations that occur at work.